The Effect of Placement, Work Environment, and Leadership on Performance Mediated Job Satisfaction - Suarni Norawati; Hardianto Hardianto; Dian Jumaisa; Zamhir Basem; Siti Syahsudarmi (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to examine the influence of job placement, work environment, and leadership on job satisfaction and performance, both directly and indirectly, as well as to examine the influence of job satisfaction on personnel performance. Methodology/approach: This study predominantly uses primary data obtained through questionnaires distributed to 46 respondents, namely personnel from the Riau Regional Police Public Relations Division. It was conducted using the SEM model with the SmartPLS program. Results/findings: Job placement has no effect on job satisfaction, while work environment and leadership have a significant effect on job satisfaction. Job placement and leadership have no significant direct effect on performance, while work environment has a significant direct effect on performance. Job satisfaction has a significant effect on performance. Job placement has no effect on performance through job satisfaction. Conclusions: Findings indicate that work environment and leadership significantly increase job satisfaction, which in turn positively impacts employee performance. Job placement, however, does not show a significant direct or indirect effect on performance through job satisfaction. Contribution: The contribution of this research is to connect the media with the police and its role as a conveyor of information to the public through the mass media. Limitation: This study was only conducted at one agency, namely the Riau Regional Police Public Relations Division, so the results cannot be generalized to other agencies, either within the police force in other regions or non-police organizations.